Comparative analysis of legal frameworks governing NGO in Egypt with applications from global practices - Ismail, Maha Mohamed (AUC Knowledge Fountain, 2017)
In recent decades, Non Governmental Organizations (NGOs) have become the flag barriers of political and social freedom, poverty alleviation, and empowerment of the poor and marginalized, as well as champions of democratization in the third world. There is an argument raised by scholars (Li, 2011, Bloodgood, 2014, Ruffner, 2015), experts, and practitioners that one of the most important elements that hinder NGOs from reaching their full potential is the legal framework regulating the operations of NGOs. This research analyzes the legal framework of selected countries from Africa, the Middle East, the United States of America as well as China, and highlights lessons learned and potential applications to the Egyptian context. 11 semi-structured interviews were conducted with selected active NGOs executives and practitioners to understand the impact of the legal framework on NGOs establishment and operations. The research findings revealed the strengths and weaknesses of law number 84 for the year 2002 and law of 2016 as perceived by NGOs. It also showed that the relation between government and NGOs not only affected the establishment of the legal framework and whether it is enabling or restricting, but also impacted the implementation of the law. It was evident that one of the major factors affecting the operations of NGOs was how the law was implemented, rather than the law articles. The eight investigated countries represent three continents, however there were commonalities between the governing laws concerning registration, funding and dissolution. Based on the outcome of the comparative study and interviews, the research presents a general review of the current status quo. This research can be used by other researchers as a starting point for a more in-depth study of the legal framework so as to better enable NGOs to play an active role in the development of Egypt.